Identifikasi, Desain Tempat Penyimpanan Sementara (TPS), dan Evaluasi Pengolahan Limbah Bahan Berbahaya dan Beracun (B3) pada Percetakkan Kaleng PT XYZ: Bahasa Inggris - Aida Mutiara; Nadinda Aisyah Kamilia; Sulistya Nengse (LRI Universitas Muhammadiyah Sorong, 2026)
The management of hazardous and toxic waste (B3) is the responsibility of companies to protect the ecosystem in the surrounding environment. This article analyzes the management of B3 waste and temporary storage designs by comparing them with existing regulations. PT XYZ is a company engaged in the printing of tin packaging, a process that produces B3 waste that needs to be handled. The data collection techniques used include secondary data, namely interviews (individual interviews) and observations. Meanwhile, secondary data collection techniques include analysis of environmental documents such as regulations and literature. The results show that the largest amount of hazardous waste generated at PT XYZ is from used majun cloth, which is 103.23 kg/day. Meanwhile, air pollution control filters produced the least amount of waste at 0.16 kg/day. The management process began with the identification of hazardous waste, temporary storage of hazardous waste, transportation to the hazardous waste storage site, weighing and recording the amount of hazardous waste, storage of hazardous waste at the hazardous waste storage site, and finally, delivery to a third party. The hazardous waste storage and arrangement are in accordance with regulations. Labeling and symbolization of each characteristic of hazardous waste produced in the factory area. The conformity score between the evaluation of hazardous waste management at PT XYZ and Regulation of the Peraturan Menteri Lingkungan Hidup No. 6 of 2021 is 72.73%.